Study of The Meaning of Lelaki, Bujang and Bujangan Words in the Utilisation of Indonesian Corpus - Yuki, Librilianti Kurnia (Jurnal Sasindo UNPAM, 2021)
This study aims to examine the meaning of the words man, single, and bachelors in the use of the Indonesian language corpus and how the semantic and pragmatic meanings of the use of the words male, single, and bachelor are seen from their collocation. The method used in this research is descriptive qualitative. Data were collected using Leipzig corpora and word sketch engine of the linguistic corpus for Indonesian. The word male appeared 69,907 times, the word single appeared 1,473 times, and the word bachelor appeared 69,907 times. The researcher uses discourse analysis for the word male, which can be used according to the meaning of the word/semantics. In a colocation sense, it turns out that men have the equivalent of nine words, while bachelors have a colocation with ten words and bachelors have a colocation with thirteen words.